Triple mental foramina: CBCT findings of an unusual anatomical variant - J John Hearty Deepak; A Nelson; C Saravana Bharathi; D Angeline Deepthi (Wolters Kluwer Medknow Publications, 2018)
The mental foramen is an important anatomic landmark located on the buccal aspect of the mandible. Evaluation of anatomical variants in the mental foramen (MF) is an important prerequisite for implant and surgical procedures involving the anterior part of the mandible body to avoid mental nerve branches injury. The most frequent variation is the presence of double mental foramen, ranging from 1.4% to 12.5%. The incidence of triple mental foramen is extremely rare ranging from 0.7% to 1.2%. Cone beam computed tomography (CBCT) is the diagnostic tool of choice for imaging the maxillofacial region, which allows accurate three-dimensional analysis of mental foramen variations. The present report describes an unusual case of triple mental foramina of the right side of the mandible in a 39-year-old south Indian male detected by CBCT.